Biomechanical effects of cement discoplasty on the lumbar spinal unit - Huang, Jiajun; Zeng, Weike; Li, Ming; Cheng, Ziying; Huang, Junshen; Liang, Changchun; Li, Yuxi; Huang, Lin (Frontiers in Surgery, 2022)
Abstract Background: Percutaneous cement discoplasty (PCD) is used to treat patients with low back and leg pain due to intervertebral disc vacuum phenomena. Whether PCD can restore lumbar spinal stability remains unknown. Objective: The purpose of our in vitro study was to evaluate the biomechanical changes brought about by PCD. Methods: Eight fresh pig lumbar spines were tested in the following order: intact, after nucleotomy, and after discoplasty. Flexion/extension, lateral bending and axial rotation were induced by pure moments. The range of motion and neutral zone were recoded. A CT scan was performed to assess the injection volume of the bone cement and to observe whether the bone cement was fractured. After removing the facet joint, the compression failure test conducted to observe the fracture of bone cement. Results: Compared with nucleotomy, ROM after discoplasty was reduced only in lateral flexion (P＜0.05). The results of the neutral zone showed that the neutral zones in flexion-extension and lateral bending were significantly reduced after discoplasty (P<0.05). The neutral zone is more sensitive to changes in lumbar stability than ROM. Bone cement slides were observed during the biomechanical test. The CT scan and compression failure test showed that bone cement fracture was more likely to occur at the puncture channel in the annulus fibrosus region. Conclusion: In all, the biomechanical study indicates that discoplasty helps enhance stability of the lumbar spine in flexion-extension and lateral bending but not in axial rotation, which explains how PCD works for low back pain. Fracture and sliding of bone cement was observed after discoplasty, and this was more likely to occur at the puncture channel in the annulus fibrosus region. This suggests that the bone cement displacement after PCD may cause compression of the nerve.